2017
DOI: 10.4254/wjh.v9.i36.1352
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sustained virologic response on chronic kidney disease progression in hepatitis C

Abstract: AIMTo determine how sustained virological response at 12 wk (SVR12) with direct acting antivirals (DAAs) for the treatment of hepatitis C virus (HCV) infection affects chronic kidney disease (CKD) progression.METHODSA retrospective analysis was performed in patients aged ≥ 18 years treated for HCV with DAAs at the VA Greater Los Angeles Healthcare System from 2014-2016. The treatment group was compared to patients with HCV from 2011-2013 who did not undergo HCV treatment, prior to the introduction of DAAs; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Despite the promising results of HCV eradication by DAA therapy in kidney transplant recipients, it remains unclear whether SVR will prevent long‐term complications of HCV infection, such as glomerulonephritis and posttransplant diabetes mellitus (PTDM) 27 . In our cohort, five patients developed PTDM before ( n = 4) or during ( n = 1) DAA therapy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Despite the promising results of HCV eradication by DAA therapy in kidney transplant recipients, it remains unclear whether SVR will prevent long‐term complications of HCV infection, such as glomerulonephritis and posttransplant diabetes mellitus (PTDM) 27 . In our cohort, five patients developed PTDM before ( n = 4) or during ( n = 1) DAA therapy.…”
Section: Discussionmentioning
confidence: 98%
“…Of note, patients who completed the 1‐year follow‐up did not show a significant decline in eGFR; in fact, many recipients showed an improvement in kidney function. Aby et al 27 evaluated the progression of native CKD after DAA therapy and compared the findings with those for untreated patients; there was no significant difference in kidney function between the two groups at the 2‐year follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…However, the HCV infection remained significant risk factor of eGFR decline after adjusting for age, gender, hypertension, diabetes, baseline eGFR and UPCR in the normal renal function subjects of our study. In addition, interventional studies have indicated that reductions of viral load were associated with improvement of renal function in patients receiving antiviral treatment 7 , 29 , 36 39 , implicating an independent role of HCV in inducing renal damage from very early stage of disease.…”
Section: Discussionmentioning
confidence: 99%
“…All approved DAAs can be used in patients with mild-tomoderate renal impairment [144], and recently the exclusion of sofosbuvir-based therapies in patients with severe renal impairment has been removed [145]. The great majority of studies published so far [146][147][148][149][150][151][152][153] have shown that DAAs are effective in lowering the risk of kidney disease in HCV-positive patients and in stabilizing/improving renal function in patients with CKD, even though the long-term impact on kidney survival is still largely unknown [93].…”
Section: Chronic Kidney Diseasementioning
confidence: 99%